Answer:
D
Step-by-step explanation:
Find (f + g)(x) then evaluate (f + g)(9)
(f + g)(x) = f(x) + g(x)
= 4x - 1 + x² - 2 = x² + 4x - 3
Now substitute x = 9 into the expression
(f + g)(9) = 9² + 4(9) - 3 = 81 + 36 - 3 = 114 → D
Functions are basically another way of expressing a way to get y or x or anything (mostly used for graphs) You will see functions like <em>f(x)=</em> <em>23y-5 </em>(that was made up). Basically the number in the parenthesis in front of the f is what you're finding. So the equation after the equal sign is how to find whatever is being found. So in this case, finding x can be pretty easy. By the way, when graphing this you have x as the run and y as the rise. <em />
sorry for taking your points
Answer:
It comes with 13.8 ounces of crackers now.
Step-by-step explanation:
12 + 15% = 13.8
The weight would be converted to 30 pounds on the moon